Identification of a water-soluble indirubin derivative as potent inhibitor of insulin-like growth factor 1 receptor through structural modification of the parent natural molecule - Cheng, Xinlai; Wölfl, Stefan (Journal of medicinal chemistry, 2017)
Indirubins have been identified as potent ATP-competitive protein kinase inhibitors. Structural modifications in the 5- and 3′-position have been extensively investigated, but the impact of substituents in 5′-position is not equally well-studied. Here, we report the synthesis of new indirubin 3′- and 5′-derivatives in the search of water-soluble indirubins by introducing basic centers. Antiproliferative activity of all compounds in tumor cells was evaluated along with kinase inhibition of selected compounds. The results show the 3′-position to tolerate large substituents without compromising activity, whereas bulk and rigid substituents in 5′-position appear unfavorable. Screening molecular targets of water-soluble 3′-oxime ethers revealed 6ha as preferential inhibitor of insulin-like growth factor 1 receptor (IGF-1R) in a panel of 22 protein kinases and in cells. Consistently, 6ha inhibited tumor cell growth in the NCI 60 cell line panel and induced apoptosis. The results indicate that the 5′-position provides limited space for chemical modifications and identify 6ha as a potent water-soluble indirubin-based IGF-1R inhibitor.
Gesehen am 04.07.2018